Ethical Codes Universities: Theory vs. Reality - Hubálek, Tomáš (Civilia, 2015)
The paper describes the problems of ethical codes universities, which guarantee the moral level of employees of the universities. In comparing these codes integrates the same features, provides examples of both positive and negative values and analyzes the largest cause of negative behavior of the academic staff.
Keywords: Code of Ethics; Morality; Universities; Social Sciences